Effects of Massages Administered by Spouses on Labor Pain and Delivery Duration among Primiparous Women - Pi-Hui Chen; Chien-Huei Kao; Su-Chen Gou; Chieh-Yu Liu; Panchalli Wang; Chia-Lung Shih (SAGE Open Nursing)
Objective To explore the effects of massages administered by spouses on labor pain and delivery duration among primiparous women. Methods This quasi-experimental study included women who were selected to give birth at the researchers’ hospital and were assigned to either to an experimental or control group based on their willingness to participate. The experimental group received the massage during the latent and active phases of labor. Pain levels during labor were measured using the Visual Analog Scale. Results A total of 100 women, with 50 in each group, were included in the analysis. During both the latent and active phases of labor, the experimental group experienced greater reductions in pain levels compared with the control group ( p  < .001). Compared with the control group, fewer participants in the experimental group needed pain relief medication, although this difference was not statistically significant (36% in the experimental group vs. 56% in the control group, p  = .07). The first stage of labor was significantly shorter for the experimental group (11.21 ± 5.25 h) than for the control group (16.06 ± 7.35 h, p  < .001). However, no significant differences in the duration of the second and third stages were observed between the two groups. Conclusion The massage administered by spouses during labor significantly reduced labor pain and shorten the duration of the first stage of labor.